2004
DOI: 10.2337/diacare.27.10.2341
|View full text |Cite
|
Sign up to set email alerts
|

The Treatment of Diabetic Gastroparesis With Botulinum Toxin Injection of the Pylorus

Abstract: OBJECTIVE -Gastroparesis is a disorder of delayed gastric emptying that is often chronic in nature. Up to 50% of type 1 diabetic subjects have symptoms of gastroparesis, which include nausea, vomiting, and early satiety. Elevated pyloric pressures may be responsible for delayed gastric emptying in diabetic subjects. Botulinum toxin inhibits the release of acetylcholine and produces transient paralysis when injected into smooth muscle. The aim of this study was to determine whether injection of the pylorus with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0
6

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(88 citation statements)
references
References 27 publications
3
79
0
6
Order By: Relevance
“…We next examined the effects of BH4 deficiency on NO release from pyloric strips in vitro. Gastric muscle strips were incubated with 10 mmol of DAHP, a specific inhibitor of GTPCH1, for 24 (Fig. 2A).…”
Section: Resultsmentioning
confidence: 99%
“…We next examined the effects of BH4 deficiency on NO release from pyloric strips in vitro. Gastric muscle strips were incubated with 10 mmol of DAHP, a specific inhibitor of GTPCH1, for 24 (Fig. 2A).…”
Section: Resultsmentioning
confidence: 99%
“…BTA injection is used therapeutically to treat human gastrointestinal disorders, including achalasia and anal fissure, at doses ranging from 100 to 300 U of the Botox formulation [21]. Doses of 200 U of Botox injected into the pylorus have been reported to improve symptoms of gastroparesis, without adverse effects [5,22]. Doses of up to 500 U of the lower-potency Dysport formulation of BTA have been injected in the stomach [6], but 500 U of Dysport has an estimated potency equivalent to 125 U of the Botox formulation [23].…”
Section: Discussionmentioning
confidence: 99%
“…In a case study involving a single patient with type 1 diabetes, Gupta and associates 16 demonstrated a return of normally coordinated peristaltic activity in the antroduodenal region after botulinum injection, with an improvement in the patient's level of nausea and vomiting. Lacy and associates 17 have shown a substantial decrease in symptom scoring in 8 type 1 diabetic patients after a botulinum injection. However, of 2 randomized controlled trials performed to date, neither found a significant difference in either symptom scoring (P = NS; P = .42) or solid or liquid gastric emptying (P = NS) between botulinum toxin and placebo.…”
Section: Discussionmentioning
confidence: 95%